Multifunctional Cotton Fabrics Coated with Banana Peel-Synthesized ZnO Nanoparticles - Rattanaburi, Parintip; Porrawatkul, Paweena; Pimsen, Rungnapa; Tongsom, Montakarn; Nuengmatcha, Prawit; Khongsai, Sunanta (Trends in Sciences, 2025)
This research presents an environmentally friendly approach for synthesizing zinc oxide (ZnO) nanoparticles using banana peel extract as a natural reducing and stabilizing agent. The synthesis avoids hazardous chemicals, aligning with green chemistry principles. The ZnO nanoparticles were characterized using XRD, SEM, EDX, TEM, and FTIR techniques, confirming their crystalline structure, uniform morphology, and successful phytochemical interaction. The ZnO nanoparticles were coated onto cotton fabrics via an ultrasonication method, ensuring even deposition. The coated fabrics demonstrated enhanced UV protection with a UV protection factor (UPF) of 82.67, categorized as excellent protection, and retained strong UV-blocking properties even after 20 washing cycles. The fabrics also exhibited significant antibacterial activity, effectively inhibiting Staphylococcus aureus (zone of inhibition: 26.17 mm) and Escherichia coli. This antibacterial performance was attributed to the release of reactive oxygen species (ROS) and Zn2+ ions, which disrupt bacterial cell walls. This study highlights the dual functionality of ZnO-coated fabrics in providing UV protection and antibacterial properties while maintaining their durability and eco-friendliness. The findings demonstrate the potential of utilizing green-synthesized nanoparticles in developing multifunctional textiles for applications in healthcare, protective clothing, and environmental sustainability. HIGHLIGHTS ZnO nanoparticles were synthesized using banana peel extract, offering an eco-friendly and sustainable method aligned with green chemistry. Cotton fabrics coated with ZnO nanoparticles showed excellent UV protection (UPF = 82.67) and antibacterial properties, retaining durability after 20 washes. The coated fabrics effectively inhibited Staphylococcus aureus and Escherichia coli, driven by reactive oxygen species (ROS) and Zn2+ ion release. This approach highlights the potential of agricultural waste in developing multifunctional, sustainable textiles for healthcare and protective clothing. GRAPHICAL ABSTRACT